Correlation between Mastery on the Simple Present Tense and Writing Descriptive Paragraph - Lidia Deviga; Radian Arum Ardhani (LETS: Journal of Linguistics and English Teaching Studies, 2022)
Some English learners might be very good at grammar English but not optimal in writing English, and vice versa. As fellow productive language skills, researching the relationship between grammar and writing skills will be very interesting. The aim of this research was to find out the correlation between mastery on the simple present tense and writing descriptive paragraph. The method that was used in this research was a quantitative research .In this research, the researcher used the subject were 42 students of the First semester Medical Record Program of STIKES Bhakti Husada Mulia Madiun in the academic year 2021/2022. There are Simple present tense and writing descriptive paragraph test were used as the instrument for collecting the data of this research. Pearson’s Product Moment Formula was used to correlate both mastery on simple present tense (variable X) and the ability in writing descriptive text (variable Y). The result showed that there was a statistically significant correlation (0.756) is higher than the r value of significant level at 5 % (0.304). Theoretically, Null Hypothesis (Ho)is rejected and Alternative Hypothesis (Ha) is accepted. The suggestion are: the students should improve their mastery on simple present tense because it can improve their ability in expressing activities in writing.